2013
DOI: 10.1002/jgrd.50639
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing moisture exchange between the Hawaiian convective boundary layer and free troposphere using stable isotopes in water

Abstract: [1] The subtropical convective boundary layer (CBL) plays a critical role in climate by regulating the vertical exchange of moisture, energy, trace gases, and pollutants between the ocean surface and free troposphere. Yet bulk features of this exchange are poorly constrained in climate models. To improve our understanding of moisture transport between the boundary layer and free troposphere, paired measurements of water vapor mixing ratio and the stable isotope ratio 18 O/ 16 O are used to evaluate moist conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 54 publications
1
75
0
Order By: Relevance
“…Aemisegger et al, 2012;Noone et al, 2013), and nonparametric functions (cf. Bailey et al, 2013) are evaluated by least squares estimation. Nonparametric characterizations of the concentration dependence are derived by fitting a locally weighted polynomial regression with R's "locfit" package (Loader, 1999).…”
Section: Statistical Methods For Characterizing and Correcting Isotopmentioning
confidence: 99%
See 1 more Smart Citation
“…Aemisegger et al, 2012;Noone et al, 2013), and nonparametric functions (cf. Bailey et al, 2013) are evaluated by least squares estimation. Nonparametric characterizations of the concentration dependence are derived by fitting a locally weighted polynomial regression with R's "locfit" package (Loader, 1999).…”
Section: Statistical Methods For Characterizing and Correcting Isotopmentioning
confidence: 99%
“…Ehhalt, 1974;Galewsky et al, 2007) -whose vapor content must be captured through a cryogenic trap for later liquid analysis in the lab -have been replaced by field experiments in which in situ observations can be made at a temporal resolution better than 0.1 Hz. Researchers using these new commercial technologies are resolving water cycle processes on a range of local-to-regional scales, investigating, for example, water recycling within the forest canopy , evapotranspiration (Wang et al, 2010) and its contribution to atmospheric moisture Aemiseggar et al, 2014), mixing and convective processes in the atmosphere Tremoy et al, 2012;Bailey et al, 2013Bailey et al, , 2015, evaporation processes in the marine boundary layer (Steen-Larsen et al, 2014b, and large-scale condensation and advection dynamics Hurley et al, 2012;.…”
Section: A Bailey Et Al: the Stability And Calibration Of Water Vapmentioning
confidence: 99%
“…Note that the transpiration component of evapotranspiration is not expected to carry high d, as it has the same isotopic composition as the soil water at steady state (Yakir and Wang, 1996;Williams et al, 2004). In addition, the free atmospheric air is characterized by a isotopically lighter vapour (He and Smith, 1999;Bailey et al, 2013;Berkelhammer et al, 2013), and the dominance of entrainment during daytime is generally associated with a δ v depletion (Lai et al, 2006;Lai and Ehleringer, 2011;Tremoy et al, 2012;Bailey et al, 2013;Berkelhammer et al, 2013). Welp et al (2012) compared six measurement locations and found that both local evapotranspiration and entrainment were involved: in some of their sites, the d daily increase was associated with a δ 18 O decrease during the early morning due to entrainment of free atmosphere into the boundary layer during convective mixing, while the subsequent slight δ 18 O increase came from evapotranspiration.…”
Section: Daytime Processes: Contribution Of Local Evaporationmentioning
confidence: 99%
“…sociated with moistening (e.g. Galewsky and Hurley, 2010;Noone et al, 2011;Tremoy et al, 2012;Samuels-Crow et al, 2014;Bailey et al, 2013Bailey et al, , 2015Dyroff et al, 2015;SteenLarsen et al, 2015;Schneider et al, 2015). Stations located in the subtropical free troposphere are key emplacements for studying the synoptical scale humid transport in the subtropics.…”
Section: Introductionmentioning
confidence: 99%
“…Stations located in the subtropical free troposphere are key emplacements for studying the synoptical scale humid transport in the subtropics. Studies based on water vapour isotope observations in the subtropical Pacific free troposphere highlight the relevance of moisture exchange between the boundary layer and the free troposphere due to shallow convection at local scale (Bailey et al, 2013). In addition, subtropical moisture is strongly affected by the mixing of air masses, with humidity properties that are defined by their condensation and evaporation history on a regional scale (Noone et al, 2011).…”
Section: Introductionmentioning
confidence: 99%